Factors that influence youth voting behavior at Dun Tanjung Dawai, Kedah / Kamil lzaly Mohd Jamal Husni and Muhammad Fitri Adnan - Mohd Jamal Husni, Kamil lzaly; Adnan, Muhammad Fitri (2018)
Many countries including Malaysia, struggle with political exclusiveness and engagement by young people in the political process. Young voters are not interested in participating in political affairs and thus do not engage in democratic process. In this study, the total population of voters in Dun Tanjung Dawai (N26), Kedah is 39,415 includes 47.90% out of 39,415 are young voters. The study is to examines the factor that influence youth voting behaviour at Dun Tanjung Dawai, Kedah. The study also depends on quantitative technique, which gives new knowledge and information of the subject research. In this study, the proposed sampling technique is nonprobability sampling technique because the element of the population must fulfill requirement in order to be selected as sample subject. The numbers of questionnaire distributed were 169 and all were completed returned and useable. The data obtained analyzed and these following findings were found out. The relationship of social media, party leader and party track record towards the youth voting behaviour that are the variables in this study were further examined. All of these relationship were found to be significant. However, the levels of youth voting behavior in at Dun Tanjung Dawai (N26), Kedah is high. The study also provides strong evidence that it is essential to raise the intention to increase the number of youth to invovle in election.